2019
DOI: 10.3892/ijmm.2019.4153
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside attenuates oxidized low‑density lipoprotein‑induced endothelial cell injury via promotion of the AMPK/SIRT1 pathway

Abstract: Oxidized low-density lipoprotein (ox-LDL)-induced endothelial damage contributes to the initiation and pathogenesis of atherosclerosis. Salidroside can alleviate atherosclerosis and attenuate endothelial cell injury induced by ox-LDL. However, the mechanisms involved in this process are not fully understood. Therefore, the purpose of the present study was to investigate the role of the adenosine monophosphate-activated protein kinase (AMPK)/sirtuin (SIRT)1 pathway in the protection of salidroside against ox-LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 61 publications
(70 reference statements)
1
29
0
Order By: Relevance
“…additionally, activation of the aMPK/SirT1 pathway protected Pc12 cells against cisplatin-induced neurotoxicity (40). The pathway has also been reported to relieve oxidized low-density lipoprotein-induced endothelial cell injury (41). These results indicated that aMPK/SirT1 signaling serves important roles in cell injury and inflammation regulation.…”
Section: Discussionmentioning
confidence: 88%
“…additionally, activation of the aMPK/SirT1 pathway protected Pc12 cells against cisplatin-induced neurotoxicity (40). The pathway has also been reported to relieve oxidized low-density lipoprotein-induced endothelial cell injury (41). These results indicated that aMPK/SirT1 signaling serves important roles in cell injury and inflammation regulation.…”
Section: Discussionmentioning
confidence: 88%
“…The results showed that as cells were exposed to the OGD for 3-7 h periods then followed by 24 h of reperfusion, and cell viability has a time-dependent reduction, which reached 55% following 5 h of OGD ( Figure 1(a) , P < 0.01 versus control group); after exposure of OGD for 4 h, the cell viability was partially improved along with the reperfusion time ( Figure 1(b) and 1(c) , P < 0.01). However, with OGD for 6 h, the cell viability partially decreased and aggravated ( Figure 1(b) – 1(d) , P < 0.01), indicating that the 5 h of OGD treatment may be the critical point for human neurons to resist ischemic injury [ 28 , 43 ]. Hence, the 4 h OGD treatment was used as the conditions of subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…And then ATP synthesis was inhibited [ 11 , 18 , 23 ]. Thus, the absence of the mitochondrial NAD+ pool causes oxidative damages and excessive ROS production [ 28 , 50 , 52 ], which aggravates mitochondria impairment, including the function of mitochondria structure, depletion of ATP production, and depolarization of MMP [ 12 , 13 ]. In our study, the results showed after OGD/R induction, the NAD+ and the ratio of NAD+/NADH level significantly decreased ( Figure 4 ), the oxidative injuries increased ( Figure 3 ) in vitro , and MMP depolarized, which was consistent with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported to protect human umbilical vein endothelial cells (HUVECs) from oxidative stress induced by ox-LDL through increasing SIRT1, FoxO1, and SOD expression and to simultaneously down-regulate MDA and LDH [69]. Meanwhile, another research concluded that salidroside protects HUVECs against ox-LDL injury through inhibiting oxidative stress and improving mitochondrial dysfunction, which were dependent on AMPK/SIRT1 pathway activation [70]. Furthermore, Xu N et al concluded that salidroside decreased the expression of inflammatory cytokines and improved LPS-induced learning memory impairments, which were involved in the SIRT1dependent Nrf-2/HO-1/NF-κB pathway [71].…”
Section: Salidrosidementioning
confidence: 99%